Biomechanical evaluation of a fiber-reinforced composite prosthesis supported by implants with and without a microthread collar design - Gökçe Meriç; Erkan Erkmen; Ahmet Kurt; Atilim Eser; Gökhan Çelik (Elsevier, 2010)
Background/purpose: A fiber-reinforced composite (FRC) resin system was introduced as an alternative for implant-retained fixed dental prostheses (FDPs); however, the stress distribution in the bone around the implants which support the FRC-FDP has so far not been reported. The aim of this study was to investigate the biomechanical behavior of FRC-FDPs supported by implants with different collar geometries. Materials and methods: A 3-dimensional finite element analysis method was selected to evaluate the stress distribution. FRC-FDPs were supported by 2 different dental implant systems with 2 distinct collar geometries: a microthread collar structure (MCS) and a non-MCS (NMCS). In separate load cases, 300-N vertical, 150-N oblique, and 60-N horizontal forces were simulated. Tensile and compressive stress values in the cortical and cancellous bone and von Mises stresses in the fixture-abutment complex, the framework, and veneer material were calculated. Results: The MCS model revealed higher compression stresses at the cortical bone than did the NMCS model under all 3 load conditions. Moreover, higher tensile stresses under the oblique loads at the cortical bone were shown with the MCS model. In each model, stresses were much higher in the implant-abutment complex than in the cortical bone, and they were very low in the cancellous bone. Conclusion: Although additional experimental and clinical studies are needed, FRC-FDPs can be considered a suitable and alternative treatment choice for an implant-supported prosthesis. The implant design and geometry affect the load-transmission mechanisms. Implants with an MCS that supports FRC-FDPs were shown to be superior in terms of the stress distribution in the bone around the implant compared to implants with an NMCS.